1998
DOI: 10.1103/physrevlett.80.30
|View full text |Cite
|
Sign up to set email alerts
|

Abelian Monopoles inSU(2)Lattice Gauge Theory as Physical Objects

Abstract: By numerical calculations we show that the Abelian monopole currents are locally correlated with the density of the SU͑2͒ lattice action. This fact is established for the maximal Abelian projection. Thus, in the maximal Abelian projection, the monopoles are physical objects; they carry the SU͑2͒ action. Calculations on the asymmetric lattice show that the correlation between monopole currents and the density of the SU͑2͒ lattice action also exists in the deconfinement phase of gluodynamics. [S0031-9007(97) The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 21 publications
3
45
0
Order By: Relevance
“…[10]. Moreover, the excess of the action associated with monopoles (46) is numerically close to the action excess around the Abelian monopoles in the Maximal Abelian gauge [12].…”
Section: Numerical Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…[10]. Moreover, the excess of the action associated with monopoles (46) is numerically close to the action excess around the Abelian monopoles in the Maximal Abelian gauge [12].…”
Section: Numerical Resultsmentioning
confidence: 73%
“…Note that the asymmetry needs not to be unity at β < β crit on the asymmetric lattice since the Lorenz invariance is explicitly broken. In order to clarify the physical relevance of the monopoles constructed consider the correlation of the local SU(2) action density and the monopole currents [12]. In particular, we define the relative excess of the action density associated with the monopole as follows:…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, this kind of measurements have been reported earlier [6]. Namely, it was shown that the non-Abelian action on the plaquettes close to the monopole trajectory is larger than the average plaquette action, S. It is easy to realize, however, that if this were true at arbitrary small distances the monopoles would be strongly suppressed by the action factor and could not condense, see, e.g., [7].…”
Section: Introductionmentioning
confidence: 92%
“…The total action of SU(2) fields is correlated with the total length of the monopole currents [35], so there exists a global correlation. The Abelian monopoles in the MaA projection are also locally correlated with the non-Abelian action density [36]. This fact shows that monopoles are some physical objects (not the artifacts of the singular gauge transformation), since by definition we call the object physical if it carries the action.…”
mentioning
confidence: 84%